(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know the reality of employing alternative evaluation tools when teaching the geography department from their point of view, and in order to achieve this goal, the researcher used the descriptive approach, the research community consisted of the geography department teachers from the College of Basic Education, Al-Mustansiriya University for the academic year (2019-2020). The researcher prepared a questionnaire As a tool for his research, its sincerity and reliability were verified and it consisted of (32) items. The researcher used a set of statistical means, including: arithmetic circles, standard deviations, and T-test for two independent samples. The research reached a set of results, the most important of them: While the second axis came with the completion files at the last rank which is the fourth and with a low degree, and after using the T-test for two independent samples to identify the presence of statistically significant differences at the level of significance of 0.05)) between the questionnaire paragraphs with respect to the gender variable, the results of the current research indicated that there are no differences attributed For the gender variable at the above level of significance, the research has reached a set of recommendations, including: - The need to educate the teaching staff on the need to employ ed The evaluation came in the process of evaluating their students during and after teaching geography at university levels because it works to increase the ability of students to interact with the scientific subject and their teacher and the teacher was able to issue the appropriate judgment on the level and ability of the student, and the researcher suggested a set of proposals, including: Conducting a study similar to the current study In other universities and other departments